След страсти: [роман] / Анна Дубчак - Дубчак Анна Васильевна (Русский романс, 2002)
Экземпляры: ф.13 (2003) / Инвентарный номер: 45480 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 79 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44